Novel Research Impact Indicators - Fenner, Martin; Lin, Jennifer (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
Citation counts and more recently usage statistics provide valuable information about the attention and research impact associated with scholarly publications. The open access publisher Public Library of Science (PLOS) has pioneered the concept of article-level metrics, where these metrics are collected on a per article and not a per journal basis and are complemented by real-time data from the social web or altmetrics: blog posts, social bookmarks, social media and other.